Economic factors affecting rice imports in Kingdom of Saudi Arabia during the period from (1989-2018) - Al-Hassan, Buthaynah Hashim; Abdalla, Samar Shamsaadin Mohamed; Elzaki, Raga Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
The Kingdom of Saudi Arabia imports rice due to limited local production as a result of scarcity of natural resources. Rice is considered the main food for both citizens and residents. Therefore, Kingdom depends on importing it from other countries such as India and Pakistan. This research aims to study the determinants of rice imports demand function in Saudi Arabia. The study has relied on secondary data collected from several published sources (Food and Agricultural Organization (FAO), World Bank and Saudi Central Bank). Autoregressive Distributed Lag (ARDL) model was used to determine the economic factors affecting rice imports. The results reveal that there is a long-term equilibrium relationship between the imports function variables. As well, there is a statistically significant relationship between rice imports and independent variables such as the Gross Domestic Production (GDP), the price of imports and the rate of inflation in the long term. Moreover, there is a statistically significant relationship between imported quantities of rice and both GDP, and the inflation rate in the short term. The results show that the error correction parameter is significant, which indicates the possibility of correcting the error in the short term to return to the long-term equilibrium. The study recommends enhancing the monetary policies that would maintain the inflation rate at reasonable levels. Furthermore, the impact of GDP on rice imports must also be taken into consideration when establishing the trade policies due to its importance and impact on both the long and short terms.